Quantitative model for the interecho time dependence of the CPMG relaxation rate in iron-rich gray matter - Jensen, J. H. (2012)
A quantitative model is proposed for computing the dependence on the interecho time of the NMR relaxation rate in iron-rich gray matter obtained with a Carr-Purcell-Meiboom-Gill sequence. The model consists of representing oligodendrocytes as identical magnetic spheres arranged in a spatially random pattern, and in approximating water diffusion as isotropic and unrestricted. Predictions of the model are calculated numerically using a Monte Carlo technique and, for the weak field limit, using an analytic formula. The model is shown to provide a good fit to experimental measurements of in vitro samples of monkey brain at field levels of 1.0 T and 1.5 T. These field levels are not sufficient to fully determine the model parameters, but it is argued that this may be possible at 3.0 T. The model is potentially of value for multiple-spin-echo MRI studies of iron-related neurodegenerative disorders, such as Parkinson's disease. In particular, the model can be applied to correlate MRI data with the cellular distribution of iron in gray matter.